1997
DOI: 10.1006/viro.1997.8736
|View full text |Cite
|
Sign up to set email alerts
|

The Coat and Cylindrical Inclusion Proteins of a Potyvirus Are Associated with Connections between Plant Cells

Abstract: The subcellular locations of two potyviral proteins, the coat (CP) and nonstructural cylindrical inclusion (CI) proteins of tobacco vein mottling virus (TVMV), during early stages in the development of systemic infections in plants, have been investigated. Ultrathin sections of newly emerged leaves in infected plants were treated with antibodies specific to these proteins and then with gold-labeled secondary antibodies and examined by electron microscopy. CI was detected near plasmodesmatal connections between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(73 citation statements)
references
References 36 publications
3
69
0
1
Order By: Relevance
“…For ISH, the protocol described by Rodriguez-Cerezo et al (26), with some modifications, was used as standard. Briefly, grids were incubated in prehybridization buffer (50% deionized formamide, 12.5% dextran sulfate, 0.2 M NaCl, 6 mM PIPES, 1 mM EDTA, 6 mg of tRNA/ml) for 2 h at 42°C and hybridized overnight at the same temperature in the same buffer containing 1 to 5 ng of the probe/l.…”
Section: Methodsmentioning
confidence: 99%
“…For ISH, the protocol described by Rodriguez-Cerezo et al (26), with some modifications, was used as standard. Briefly, grids were incubated in prehybridization buffer (50% deionized formamide, 12.5% dextran sulfate, 0.2 M NaCl, 6 mM PIPES, 1 mM EDTA, 6 mg of tRNA/ml) for 2 h at 42°C and hybridized overnight at the same temperature in the same buffer containing 1 to 5 ng of the probe/l.…”
Section: Methodsmentioning
confidence: 99%
“…In combination with ultrastructural analyses and genetic data Carrington et al (1998) results support a model in which Potyvirus CI protein interacts directly with PD and capsid protein within ribonucleoprotein complexes to facilitate Potyvirus cell-tocell movement. Ultrastructural research of tissues at an early stage of infection with immunogold labeling of specific Potyvirus proteins, have supported the role CI in local transport with cooperation in CP (Rodriguez-Cerezo et al 1997;Roberts et al 1998). Observation of young tobacco leaves infected with TVMV (Tobacco vein mottling virus; Rodriguez-Cerezo et al 1997) or cells during advanced PSbMV (Pea seed-borne mosaic virus) infection in pea cotyledons showed that cytoplasmic inclusions immunolabeled for CI protein and CP were attached to the plasma membrane, close to or over the plasmodesmal openings.…”
Section: Potyviruses Components Of Transport Networkmentioning
confidence: 93%
“…Ultrastructural research of tissues at an early stage of infection with immunogold labeling of specific Potyvirus proteins, have supported the role CI in local transport with cooperation in CP (Rodriguez-Cerezo et al 1997;Roberts et al 1998). Observation of young tobacco leaves infected with TVMV (Tobacco vein mottling virus; Rodriguez-Cerezo et al 1997) or cells during advanced PSbMV (Pea seed-borne mosaic virus) infection in pea cotyledons showed that cytoplasmic inclusions immunolabeled for CI protein and CP were attached to the plasma membrane, close to or over the plasmodesmal openings. The plasmodesmal aperture contained CP and also viral RNA during TVMV tobacco infection.…”
Section: Potyviruses Components Of Transport Networkmentioning
confidence: 93%
“…The potyvirus CI has been suggested to play a role in cell to cell movement (Laín et al 1990;Eagles et al 1994;Klein et al 1994). High-resolution ultrastructural analyses indicate that CI forms the cone-shaped structures at the cell periphery adjacent to PD (Rodríguez-Cerezo et al 1997;Roberts et al 1998Roberts et al , 2003. In the case of the newly found P3N-PIPO protein, it has been shown that mutation of the putative SMV PIPO domain impeded cell-to-cell movement (Wen et al,2010) and that P3N-PIPO mediated the formation of CI conical structures at PD (Wei et al, 2010b).…”
Section: Smv Cell-to-cell and Long-distance Movementmentioning
confidence: 99%